2008
DOI: 10.1007/s11262-008-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of porcine circovirus type 2 (PCV2) pre- and post-epizootic postweaning multisystemic wasting syndrome (PMWS)

Abstract: The porcine circovirus type 2 (PCV2) genome encodes three major open reading frames (ORFs) encoding the replicase proteins (ORF1), the viral capsid protein (ORF2), and a protein with suggested apoptotic activity (ORF3). Previous phylogenetic analyses of complete genome sequences of PCV2 from GenBank have demonstrated 95-100% intra-group nucleotide sequence identity. However, although these isolates were readily grouped into clusters and clades, there was no correlation between the occurrence of specific PCV2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 26 publications
2
40
0
1
Order By: Relevance
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15], China [17,21,38], Cuba [29], Denmark [12], Germany [30], Japan [32], Korea [1,2,19,20], Slovakia [37], Spain [10], Sweden [33], Switzerland [39], Thailand [18] and the U.S.A. [6,23]. PCV2b might be more pathogenic than PCV2a [16,32].…”
mentioning
confidence: 99%
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15], China [17,21,38], Cuba [29], Denmark [12], Germany [30], Japan [32], Korea [1,2,19,20], Slovakia [37], Spain [10], Sweden [33], Switzerland [39], Thailand [18] and the U.S.A. [6,23]. PCV2b might be more pathogenic than PCV2a [16,32].…”
mentioning
confidence: 99%
“…The interaction between poRGS16 and ORF3 varied for ORF3 proteins from the three different genogroups of PCV2 (Segalés et al, 2008;Timmusk et al, 2008) and was barely detectable for either the corresponding region of ORF3 from PCV1 (315 bp) or the full-length PCV1 ORF3 (612 bp). Interestingly, PCV1 is regarded as non-pathogenic, whereas several studies suggest that genogroups of PCV2 can differ in their contribution to the development of PMWS (Carman et al, 2008; Gagnon et al, 2007;Timmusk et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PCV1 is regarded as non-pathogenic, whereas several studies suggest that genogroups of PCV2 can differ in their contribution to the development of PMWS (Carman et al, 2008;Gagnon et al, 2007;Timmusk et al, 2008). It was recently shown that mutations within the genome of PCV2 were silent in the ORF coding for the replicase but induced amino acid substitutions in the ORF3 in the opposite transcription orientation (Timmusk et al, 2008). Thus, PCV2 could theoretically retain the unmodified Rep and Rep9 proteins despite alterations in the ORF3 protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations